2003
DOI: 10.1089/104454903322216644
|View full text |Cite
|
Sign up to set email alerts
|

cis-Acting Elements in the Hepatocyte Growth Factor-Like Protein Gene Regulate Kidney and Liver-Specific Expression in Mice

Abstract: Previous studies from our laboratory demonstrated that the hepatocyte-specific transcriptional activity of the hepatocyte growth factor-like protein/macrophage stimulating protein (HGFL) promoter is modulated in HepG2 cells by the first 135 base pairs (bp) upstream of the HGFL transcriptional start site. Gel mobility shift and transactivation assays demonstrated that hepatocyte nuclear factor-4 (HNF-4) binds to this region and is responsible, in part, for the liver-specific expression of this gene in HepG2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Promoter analyses have suggested that the transcription factor hepatocyte nuclear factor-4 is important for the liver-specific expression of HGFL (Waltz et al, 1996). Specific elements in the first intron of HGFL have also been found to regulate liver-and kidney-specific expression (Wetzel et al, 2003). In addition, experiments performed in one cell type derived from large-cell lung carcinoma have demonstrated the ability of mutant p53 to associate with the HGFL promoter and repress its transcriptional activity, leading to a decrease in HGFL mRNA and secreted protein and increased cell survival after exposure to a chemotherapeutic agent (Zalcenstein et al, 2006).…”
Section: Ron Ligand Structure and Functionmentioning
confidence: 99%
“…Promoter analyses have suggested that the transcription factor hepatocyte nuclear factor-4 is important for the liver-specific expression of HGFL (Waltz et al, 1996). Specific elements in the first intron of HGFL have also been found to regulate liver-and kidney-specific expression (Wetzel et al, 2003). In addition, experiments performed in one cell type derived from large-cell lung carcinoma have demonstrated the ability of mutant p53 to associate with the HGFL promoter and repress its transcriptional activity, leading to a decrease in HGFL mRNA and secreted protein and increased cell survival after exposure to a chemotherapeutic agent (Zalcenstein et al, 2006).…”
Section: Ron Ligand Structure and Functionmentioning
confidence: 99%